2018
DOI: 10.1016/j.tre.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate modeling and analysis of regional ocean freight rates

Abstract: In this paper, we propose a new multivariate model for the dynamics of regional ocean freight rates. We show that a cointegrated system of regional spot freight rates can be decomposed into a common non-stationary market factor and stationary regional deviations. The resulting integrated CAR process is new to the literature. By interpreting the common market factor as the global arithmetic average of the regional rates, both the market factor and the regional deviations are observable which simplifies the cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Tsioumas et al [12] developed a multivariate vector autoregressive model with exogenous variables (VARX) to improve the forecasting accuracy of the BDI, and they found that the VARX model outperforms the ARIMA. Adland et al [13] presented cointegrated time series models in continuous and discrete time to analyze the dynamics of regional ocean freight rates.…”
Section: Introductionmentioning
confidence: 99%
“…Tsioumas et al [12] developed a multivariate vector autoregressive model with exogenous variables (VARX) to improve the forecasting accuracy of the BDI, and they found that the VARX model outperforms the ARIMA. Adland et al [13] presented cointegrated time series models in continuous and discrete time to analyze the dynamics of regional ocean freight rates.…”
Section: Introductionmentioning
confidence: 99%
“…In-turn this helps to decrease inventory carrying cost for both, the ultimate customer as well as the logistics operator. It also helps to utilize all the resources optimally with decreased transit time [41]. MMLP contributes in equitable growth of all modes of transportation, proper utilization of pooled assets like railways.…”
Section: B Multimodal Logistics Parks (Mmlp)mentioning
confidence: 99%
“…In Benth et al [14] and García et al [15], a CARMA process models the spot price in the electricity market, while in Benth et al [6] and Benth and Benth [7] it models weather variables, such as temperature and wind speed. Finally, Andresen et al [16] apply CARMA processes to interest rates modeling and [17] to the dynamics of regional ocean freight rates.…”
Section: Introductionmentioning
confidence: 99%